Hydration of Camphene over PW-SBA-15-SO3H - José Castanheiro (Molecules, 2022)
The hydration of camphene was carried out over SBA-15 with sulfonic acid groups and tungstophosphoric acid at 50 °C. The main product of camphene hydration was isoborneol, with camphene hydrate and borneol as byproducts. The catalytic activity increased with the amount of tungstophosforic acid (PW) immobilized on the silica support until a maximum, which was obtained with the PW4-SBA-15-SO3H material (16.4 wt.%). When the amount of PW immobilized on SBA-15 increased (PW5-SBA-15-SO3H, 21.2 wt.%), the catalytic activity decreased. The catalytic activity of PW4-SBA-15-SO3H increased with the water content of the solvent, until a maximum was reached with 50% water. With higher water concentrations, a decrease in the catalytic activity was observed. The selectivity to isoborneol was 90% at 99% camphene conversion in the presence of the PW4-SBA-15-SO3H catalyst. The catalytic stability of the PW4-SBA-15-SO3H material during camphene hydration was studied by performing consecutive batch runs with the same catalyst sample. After the third run, a trend towards stabilized catalytic activity was observed. A kinetic model is also proposed.